Anatomical Basis of the Myofascial Trigger Points of the Gluteus Maximus Muscle. (16th November 2017) - Akamatsu, Flavia Emi; Yendo, Tatiana Mina; Rhode, Ciro; Itezerote, Ana Maria; Hojaij, Flávio; Andrade, Mauro; Hsing, Wu Tu; Jacomo, Alfredo Luiz
Abstract : Myofascial pain syndrome is characterized by pain and limited range of motion in joints and caused by muscular contracture related to dysfunctional motor end plates and myofascial trigger points (MTrPs). We aimed to observe the anatomical correlation between the clinically described MTrPs and the entry point of the branches of the inferior gluteal nerve into the gluteus maximus muscle. We dissected twenty gluteus maximus muscles from 10 human adult cadavers (5 males and 5 females). We measured the muscles and compiled the distribution of the nerve branches into each of the quadrants of the muscle. Statistical analysis was performed by using Student's t -test and Kruskal-Wallis tests. Although no difference was observed either for muscle measurements or for distribution of nerve branching among the subjects, the topography of MTrPs matched the anatomical location of the entry points into the muscle. Thus, anatomical substract of the MTrPs may be useful for a better understanding of the physiopathology of these disorders and provide basis for their surgical and clinical treatment.